Analysis of Ship Motion Response to Hull Line Redesign of The Manado Prototyped Small Purse Seiner - Dien, Heffry Veibert; Pamikiran, Revols Dolfi Christian; Manu, Lusia; Undap, Nani Ingrid Jacquline; Pangalila, Fransisco Philep Theodorus; Manoppo, Lefrand (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
Hull line determines the ship motions in adapting to the ocean conditions, and therefore, ships require a flexibly appropriate hull line to have a highly safe sailing trip. This study aims to determine influence of small purse-seiner hull line redesign on the ship’s motion, namely rolling, heaving, and pitching which can be observed as a Response Amplitude Operator (RAO) due to the sea conditions. The hull lines were redesigned by manipulating the ship’s breadth (B) and depth (D) based on the Manado prototype, resulting in three new hull forms (ships B, C, D) and one prototype control (ship A). Data input and simulation used the Maxsurf Modeler Advanced and Maxsurf Motions Advanced applications to analyze motion responses at different wave angles (head sea 180°, bow quartering sea 135°, and beam sea 90°) under average load and service speed conditions. The findings demonstrated that each ship had a unique RAO for heave, roll, and pitch motion. In heave and pitch motion, ship D had a best RAO, but in roll motion, ship C had the best RAO. The rolling and pitching motions of all ships have met the minimum standard of the general operability limiting criteria for ships at all conditions, while the rolling motion at the wave coming of 90° was met at the slight and moderate conditions. Keywords: Heaving motion, North Sulawesi-Indonesia, pitching motion, rolling motion, ship motion